Mapping of export signals of Pseudomonas aeruginosa pilin with alkaline phosphatase fusions. - Strom, M S (1987)
Pili of Pseudomonas aeruginosa are assembled from monomers of the structural subunit, pilin, after secretion of this protein across the bacterial membrane. These subunits are initally synthesized as precursors (prepilin) with a six-amino-acid leader peptide that is cleaved off during or after membrane traversal, followed by methylation of the amino-terminal phenylalanine residue. This report demonstrates that additional sequences from the N terminus of the mature protein are necessary for membrane translocation. Gene fusions were made between amino-terminal coding sequences of the cloned pilin gene (pilA) and the structural gene for Escherichia coli alkaline phosphatase (phoA) devoid of a signal sequence. Fusions between at least 45 amino acid residues of the mature pilin and alkaline phosphatase resulted in translocation of the fusion proteins across the cytoplasmic membranes of both P. aeruginosa and E. coli strains carrying recombinant plasmids, as measured by alkaline phosphatase activity and Western blotting. Fusion proteins constructed with the first 10 amino acids of prepilin (including the 6-amino-acid leader peptide) were not secreted, although they were detected in the cytoplasm. Therefore, unlike that of the majority of secreted proteins that are synthesized with transient signal sequences, the membrane traversal of pilin across the bacterial membrane requires the transient six-amino-acid leader peptide as well as sequences contained in the N-terminal region of the mature pilin protein.